2015
DOI: 10.1186/s12871-015-0082-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound versus anatomical landmarks for caudal epidural anesthesia in pediatric patients

Abstract: BackgroundCaudal block is easily performed because the landmarks are superficial. However, the sacral hiatus is small and shallow in pediatric patients. In the present study, we evaluated under general anesthesia whether the distance between the bilateral superolateral sacral crests increased with growth, whether an equilateral triangle was formed between the apex of the sacral hiatus and the bilateral superolateral sacral crests, and whether expansion of the epidural space could be confirmed by ultrasound.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
(12 reference statements)
1
17
0
Order By: Relevance
“…In addition, the available caudal epidural space volume must be estimated preoperatively, so that high block complications are avoided [6]. Ultrasound is a safe, non-invasive and simple method of examination of the exact sacral anatomy, identification of sacral variations and accurate estimation of the volume of epidural space [1]. The use of ultrasonography for the navigation of needle placement into the caudal epidural space increases success rates by 100% [20].…”
Section: Clinical Significance In Anaesthesiologymentioning
confidence: 99%
“…In addition, the available caudal epidural space volume must be estimated preoperatively, so that high block complications are avoided [6]. Ultrasound is a safe, non-invasive and simple method of examination of the exact sacral anatomy, identification of sacral variations and accurate estimation of the volume of epidural space [1]. The use of ultrasonography for the navigation of needle placement into the caudal epidural space increases success rates by 100% [20].…”
Section: Clinical Significance In Anaesthesiologymentioning
confidence: 99%
“…Caudal anesthesia as a supplementary mode of analgesia has been considered more appropriate for gynecological surgery, and many studies have shown that the application of ultrasound has increased the safety, ease, and consistency of a caudal block analgesia [9][10][11][12] . The blockade level is an important factor to determine adequate intraoperative analgesia during regional blocks in cesarean section 29 .In our study, we changed the epidural puncture point L 2-3 or L 3-4 to T 11 -T 12 for epidural anesthesia combined with caudal anesthesia, and 10 mL of 0.75% ropivacaine and 20 ml of 0.25% ropivacaine were administrated in epidural and sacral canal respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A single point epidural block can't achieve such a wide range of nerve blocking. Caudal anesthesia as a supplementary mode of analgesia has been considered more appropriate for gynecological surgery, and many studies have shown that the application of ultrasound has increased the safety, ease, and consistency of a caudal block analgesia [9][10][11][12] . Thus we speculated that the epidural anaesthesia within T 11 -T 12 intervertebral space combined with caudal block anesthesia could achieve satisfactory anesthesia for cesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…In neonates, the incompletely ossified spinous processes, minimal fat aids in interrogation of the space by ultrasound compared to older kids and adults. The good resolution of image, lack of ionizing radiation and potential for real time guidance makes ultrasound a valuable tool for performing LP in neonates [48,56].…”
Section: Current Topics In Intensive Care Medicinementioning
confidence: 99%